The role of Japanese local governments in stabilisation policy - Werner Pascha; Frank Robaschik (Gerhard-Mercator-Universität Duisburg, Institut für Ostasienwissenschaften, 2001)
Local governments in Japan account for about 80 per cent of general government spending when excluding social security expenditures. Therefore, for the implementation of fiscal policy it is important how local governments will behave. On the basis of the economic theories on fiscal federalism it is generally rational for local government entities, especially smaller ones, not to participate in the stabilisation policy of the central government and to take a free rider position. Such a behaviour would imply a substantial reduction or even an offsetting of the effects of a stabilisation policy of the central government. As for empirical evidence, a procyclical behaviour of local entities was observed in several countries, among them Germany. We show that in Japan this was not the case and that so far local governments do participate in the stabilisation efforts of the central government. In a second step we show the institutional arrangements that have enabled the central government to influence the fiscal behaviour of the local governments accordingly. Will recent regulatory changes and the enourmous debt level have a significant impact? We argue that although from April 2000 some legal changes in the direction of decentralisation were enforced, many influence mechanisms remained intact and thus the changes weaken the established system, but did not break it up altogether.
Keywords: 330; local government borrowing; intergovernmental fiscal relations; Japan; federalism; fiscal equalisation; fiscal policy; government debt; local allocation tax; local autonomy; public finance; stabilisation policy